2017
DOI: 10.2147/vhrm.s115080
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based review on urate-lowering treatments: implications for optimal treatment of chronic hyperuricemia

Abstract: Several studies suggest that chronic hyperuricemia, the main precursor of gout, is involved in the pathogenesis of different systemic disorders that affect cardiovascular and renal systems, such as hypertension, obesity, hypercholesterolemia, atherosclerosis, metabolic syndrome, chronic heart failure, and chronic kidney disease. Recent epidemiological evidence has shown an increasing trend in the prevalence of hyperuricemia and gout in the Western world: a number of population-based studies estimate a prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 50 publications
1
56
0
5
Order By: Relevance
“…e present study showed a rate of 19.0% for 1-year all-cause mortality in elderly patients with ACS, which is consistent with a previous report [21]. A large body of evidence indicates that hyperuricemia is an emerging CVD risk factor [22,23], besides traditional risk factors for CVD. e results of the present study showed that hyperuricemia is associated with the female sex, arterial hypertension, AF, lower HDL-cholesterol, elevated serum creatinine, and in-hospital cardiac complications.…”
Section: Cardiovascular Erapeuticssupporting
confidence: 93%
“…e present study showed a rate of 19.0% for 1-year all-cause mortality in elderly patients with ACS, which is consistent with a previous report [21]. A large body of evidence indicates that hyperuricemia is an emerging CVD risk factor [22,23], besides traditional risk factors for CVD. e results of the present study showed that hyperuricemia is associated with the female sex, arterial hypertension, AF, lower HDL-cholesterol, elevated serum creatinine, and in-hospital cardiac complications.…”
Section: Cardiovascular Erapeuticssupporting
confidence: 93%
“…The same pertains to the efficiency of hypouricemic drugs [13]. The LIFE study showed that a decrease in SUA was associated with better long-term results in patients who were treated with losartan, as compared to those who took atenolol [14].…”
Section: Introductionmentioning
confidence: 99%
“…(Goldman et al, 2001;Hershfield et al, 2010). Along with the overproduction of UA, the occurrence of oxidative stress is always noted, which damages organ function (Bove, Cicero, Veronesi, & Borghi, 2017).…”
Section: Introductionmentioning
confidence: 99%